Social capital, household welfare and poverty in Indonesia - Grootaert, Christiaan 1950- (Policy research working paper, 1999)
It pays for poor households to participate actively in local associations. At low incomes, the returns to social capital are higher than returns to human capital. At higher incomes, the reverse is true